STUDIES ON THE OCCURRENCE OF ENTERIC BACTERIA IN THE ESTUARINE WATERS ALONG MANGALORE COAST - SRIKANTAIAH, M; SHENOY, M G; MOHANKUMAR, K C (Fishery Technology, 2017)
Occurrence of enteric bacteria in water, sediment and shellfishes of Mulki, Pavanje, Gurpur and Netravathi estuaries of the Mangalore coast is reported. 70 water samples, 71 sediment samples and 37 shellfish samples were analysed in 18 months. Total bacterial load in sediment and shellfishes was found to be more than that in water samples. The total bacterial load was not very high. However, enterococci, particularly coliforms in sediments, water and shellfishes were found to be quite high, indicative of faecal pollution. The incidence of Salmonella spp. was recorded in all the estuaries except the Mulki Estuary.